Exploring organizational management of extrovert school leadership - Syed Kamran Ali Shah; Muqaddas Butt; Ayaz Muhammad Khan; Muhammad Zeeshan; Aatika Aziz (Institute of Advanced Engineering and Science, 2023)
The study aimed at determining the personality traits of extroversion and introversion of school leadership and evaluating their organizational management in Federal Government Educational Institutions (FGEIs). A quantitative research design along with a positivist paradigm was followed. The total population consisted of 68 school principals and 592 teachers of FGEIs in the Gujranwala, Fazaia, and Lahore Regions from which 54 principals and 381 teachers were selected using a random sampling technique. Eysenck Personality Inventory (EPI) was deployed to collect information about personality traits and data regarding organizational management, the researchers used a self-developed questionnaire. Pearson correlation r and t-tests were deployed for inferential stats. The results showed that extrovert school leaders perform their duties well as they hold a clear concept of the vision and mission of the organization, set up an accepted procedure to plan short-term and long-term goals, share responsibilities with all stakeholders following their skills, and ensure the smooth functioning of the school with the help of all stakeholders. In comparison, introverted school principals show less interest in the organizational management of their schools. Moreover, organizational management of school leadership has a positive correlation with the personality trait of extroversion and a significant difference can be seen in organizational management of an extrovert and an introvert school principal. It was recommended that the performance indicators and standards of school principals should be effectively communicated to school leadership. Introvert school leadership should be provided with the necessary psychological training to reduce this shortcoming of personality.